Altered brain spontaneous activity and connectivity network in irritable bowel syndrome patients: A resting-state fMRI study. Issue 6 (June 2015) - Ma, Xiaofen; Li, Shumei; Tian, Junzhang; Jiang, Guihua; Wen, Hua; Wang, Tianyue; Fang, Jin; Zhan, Wenfeng; Xu, Yikai
Highlights We aimed to provide evidence that brain functional alterations induced by irritable bowel syndrome (IBS) are not limited to local changes but also express at a level of functional integration using resting-state functional magnetic resonance imaging (R-fMRI). IBS patients have decreased amplitude of low-frequency fluctuation (ALFF) in cognitive and pain regulatory and somatosensory regions. Functional connectivity analysis revealed the increased connectivity between cingulate and frontal cortex in the IBS patients.